The Impact of Prior Knowledge on Adolescents' Sexual and Reproductive Health Behavior Amidst the Covid-19 Pandemic: The Case of Kakamega County, Kenya (Proceedings of the International Conference on Future of Education, 2022)
Adolescents (aged between 10 and 19 years) go through significant physical, physiological, and psychosocial changes from childhood to adulthood during this period. There are indications that during the COVID-19 pandemic, adolescents experienced a myriad of challenges as reported by various forms of media. These challenges included teenage pregnancies/ motherhood and early marriages amongst girls, drug and substance abuse, and other social deviancies that came with devastating consequences, notably a surge in school dropout, which shuttered their dreams for a better future. During the outreach activities by the African Women in Science and Engineering (AWSE), MMUST chapter, a gap for research in the realm of Sexual and Reproductive Health of adolescents was established, necessitating this study. The objective guided the study: To establish how prior Knowledge on Sexual and Reproductive Health (ASRH) shaped their behavior in the wake of the COVID-19 Pandemic. The study adopted a Mixed Methods Research (MMR) approach, drawing on the strengths of both quantitative and qualitative paradigms, with a sample of 340 adolescents. The sampling techniques employed were multi-stage, purposive, stratified, and simple random sampling. The data collection tools included questionnaires, interviews schedules, and Focus Group Discussions (FGDs). Quantitative data were analyzed descriptively and inferentially using SPSS version 20 while qualitative data were analyzed thematically and used in triangulating quantitative findings. Results showed that 90% of adolescents had Knowledge of sexual and reproductive health, an indication that there was a10% knowledge gap. Significant differences were recorded across gender (Chi=4.715, p=0.030); age (Chi=8.775, p=0.012); religion (Chi=10.204, p=0.017) and education level (Chi=14.338, p=0.008), among others. Results further showed that Knowledge on ASRH had a positive impact on adolescents' behavior as a smaller proportion (34.3%) of those with the Knowledge engaged in sexual relationships, compared to 42.9% of those without the Knowledge. This however, did not translate to better behavior as manifested in a surge in unsafe abortions, failure to embrace contraception, and inability to seek appropriate medical care. The study therefore recommends development and implementation of appropriate regulatory frameworks and policies to empower youth through appropriate education programs in order to mitigate the risks and challenges encountered by adolescents.
Keywords: adolescent; sexual & reproductive health knowledge; behavior; COVID-19 pandemic